An active and stable multifunctional catalyst with defective UiO-66 as a support for Pd over the continuous catalytic conversion of acetone and hydrogen. Issue 1 (21st December 2020) - Hu, Yingjie; Mei, Yuxin; Lin, Baining; Du, Xuhong; Xu, Fan; Xie, Huasheng; Wang, Kang; Zhou, Yonghua
Abstract : The one-pot synthesis of methyl isobutyl ketone (MIBK) and methyl isobutyl methanol (MIBC) from acetone and hydrogen is a typical cascade reaction comprised of aldol condensation-dehydration-hydrogenation. Abstract : The one-pot synthesis of methyl isobutyl ketone (MIBK) and methyl isobutyl methanol (MIBC) from acetone and hydrogen is a typical cascade reaction comprised of aldol condensation-dehydration-hydrogenation. Pd loss and aggregation during long term operation are typical problems in industrial application. In this paper, an active and stable catalyst was achieved with defective UiO-66 as a support for Pd, which was synthesized with the ratio 15 : 1 of ZrOCl2 ·8H2 O to ZrCl4 as Zr-precursors. The resultant Pd catalyst remained active for at least 1000 h with a MIBK + MIBC selectivity of 84.87–93.09% and acetone conversion of 45.26–53.22% in a continuous trickle-bed reactor. Besides the increased Brønsted acid amount generated by the defect sites was favorable for the activity, the cavity confinement in the UiO-66 ( R = 15 : 1) structure also efficiently prevented Pd loss and aggregation during the long term run. The contrast of the characterization of the fresh and used Pd/UiO-66 ( R = 15 : 1) indicated that the deactivation of the catalyst was attributed to carbonaceous accumulation on the catalyst surface, which could be easily regenerated by calcination. This work supplied a new alternative for the design and utilization of industrial catalysts for MIBK and MIBC synthesis.